Expanding the scope of alcohol dehydrogenases towards bulkier substrates: Stereo- and enantiopreference for α,α-dihalogenated ketones - Kedziora, Kinga (2014)
Alcohol dehydrogenases (ADHs) were identified as suitable enzymes for the reduction of the corresponding α,α-dihalogenated ketones, obtaining optically pure β,β-dichloro- or β,β-dibromohydrins with excellent conversions and enantiomeric excess. Among the different biocatalysts tested, ADHs from Rhodococcus ruber (ADH-A), Ralstonia sp. (RasADH), Lactobacillus brevis (LBADH), and PR2ADH proved to be the most efficient ones in terms of activity and stereoselectivity. In a further study, two racemic α-substituted ketones, namely α-bromo- α-chloro- and α-chloro-α-fluoroacetophenone were investigated to obtain one of the four possible diastereoisomers through a dynamic kinetic process. In the case of the brominated derivative, only the (1R)-enantiomer was obtained by using ADH-A, although with moderate diastereomeric excess (>99 % ee, 63 % de), whereas the fluorinated ketone exhibited a lower stereoselectivity (up to 45 % de). Bulking up: A series of β,β-dihalohydrins are obtained through alcohol dehydrogenase (ADH) catalyzed bioreduction of the synthesized α,α-dihalogenated ketones. Two racemic acetophenone derivatives are also subjected to this protocol to obtain stereoenriched alcohols through dynamic kinetic resolution (DKR). © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.